Grammar Learning Strategies Employed by Pre-Service English Teachers of a University - Fauziah Fauziah; Afrianto Daud; Dahnilsyah Dahnilsyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
This study aims to find out what kinds of grammar learning strategies are mostly employed by a group of pre-service English teachers. The subjects of this study were second-year students of the English Study Program, Faculty of Teacher Training and Education of a university in Indonesia. This study used a total population sampling technique which means the entire population is used as the sample (n= 90 students). Data were collected using a set of questionnaires consisting of three types of grammar learning strategies, namely cognitive strategies, metacognitive strategies and socio-affective strategies. This study found that the pre-service English teachers employed various strategies when they learn and use grammar. The three types of grammar learning strategies appeared to be the commonly used strategies, with cognitive strategies as the most frequently employed by the pre-service English teachers as indicated by the average score of 4.12 and the lowest strategy was metacognitive strategy indicated by the average score of 3.86.